Aplikasi Tempat Sampah Pintar Dengan Notifikasi Menggunakan Telegram (Studi Kasus Dinas Lingkungan Hidup Kabupaten Ende) - Benediktus Yoseph Bhae; Valerius Opa; Kristianus Jago Tute (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The problem at the Ende Regency Environmental Service is that waste disposal in the environment is still carried out conventionally, namely with ordinary trash cans. The purpose of this study is to design a smart trash can application with notifications using telegram. The method used in this study is an experimental method, which can be said as a research method used to seek certain treatments for others in uncontrolled conditions. The data collection technique is by conducting interviews, observations, and literature studies. User testing directly in the smart trash can. The result of this research is the ease of disposing of garbage in its place because there is no smart trash can that opens automatically. The conclusion of this research is to be able to design a smart trash can application with notifications using telegram